ASSISTING WHEELCHAIR USERS ON BUS RAMPS: A POTENTIAL CAUSE OF LOW BACK INJURY AMONG BUS DRIVERS - Bareria, Piyush; Shin, Gwanseob (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
Manual assistance to wheelchair-users while boarding and disembarking a bus may be an important risk factor for musculoskeletal disorders of bus drivers, but no study has yet assessed biomechanical loads associated with the manual assist operations. In this study, off-duty bus drivers simulated wheelchair-user assisting operations using forward and backward strategies for boarding and disembarking ramps. Low-back compression and shear forces, shoulder moments and percent population capable of generating required shoulder moment were estimated using the University of Michigan Three-Dimensional Static Strength Prediction Program. L4-L5 compression force ranged from 401.6 N for forward boarding to 2169.3 N for backward boarding (pulling), and from 2052.4 N for forward disembarking to 434.2 N for backward disembarking (pushing). The shoulder moments were also consistently higher for the pushing tasks. It is recommended that bus drivers adopt backward boarding and forward disembarking strategies to reduce the biomechanical loads on the low back and shoulder.